"Golden Intersection" in performance indicators of higher education institutions of Ukraine - Totska , Olesia (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2024)
The domestic system of higher education is obliged to ensure quality, transparency and mobility. The purpose of the article is to identify the “golden intersection” in the indicators of the quality of the provision of educational-scientific services by higher education institutions (HEIs) of Ukraine based on automated ABC analysis. The methodology for conducting automated ABC analysis using the Microsoft Excel spreadsheet processor has been developed; an ABC analysis of the quality indicators of the provision of educational and scientific services by HEIs of Ukraine was carried out in terms of the total number of prepared prize winners of the All-Ukrainian student olympiad and the All-Ukrainian contest of student scientific works; the hypothesis about the existence of a “golden intersection” in quality indicators of the provision of educational and scientific services by HEIs of Ukraine was tested. Group A included 84 HEIs of Ukraine (38.53% of the total number), which had from 15 to 146 prize winners. The accumulated share of prize winners of this group of HEIs in their total number was 80.97%. Group B included 56 HEIs of Ukraine (25.69% of the total number), which had from 7 to 14 prize winners. Their contribution to the total number of prize winners was 14.19%. Group C included 78 HEIs of Ukraine (35.78% of the total number) with the number of prize winners from 1 to 6. The share of graduates from HEIs of this group in the total number was 4.84%. In order to test the hypothesis of the existence of a “golden intersection”, it was assumed that HEIs from groups B and C would have a larger value, HEIs from group A would have a smaller value. The ratio of 134/84 HEIs was obtained. The calculated values turned out to be extremely close to the reference “golden” number φ=1.618.